THE RESPONSE OF HYPERMARKET BUILDING FOR ADAPTABILITY IN HOUSING DEVELOPMENTS - Asharhani, Imaniar Sofia; Kusuma, Adriyan; Agriza, Kurnia Fajar (MODUL, 2024)
This paper aims to explore the key factors to assess the adaptability of hypermarkets into residential units. The study focuses on practice studies in Indonesia, specifically Transmart, Trans Icon and Trans Park all of which are former Carrefour hypermarkets undergoing redevelopment. The research investigates the adaptive capacity and adaptive response of these redevelopments by analyzing factors such as location, economic viability, structural constraints, and regulatory compliance, which are critical to determining the feasibility of such adaptations. The methodology involves a comprehensive review of previous literature, secondary data analysis, and an evaluation of overlapping adaptability assessment instruments. The methodology involves a comprehensive review of previous literature, secondary data analysis, and an evaluation of overlapping adaptability assessment instruments. From these instruments, the study explores their implementation in practice within Indonesia, focusing on case studies of hypermarkets. This is followed by identifying adaptation responses from the owners' perspective, particularly regarding their strategies and decision-making processes in adapting hypermarkets for mixed-use functions. Data collection utilizes Street View Imagery (SVI) to analyze spatial changes, locational factors, and patterns of transformation, providing a visual representation of adaptability. Findings reveal the study identifies two types of hypermarkets adaptation response: those with limited areas, where expansion is primarily vertical with similar functions, and those with larger areas that allow for horizontal expansion. Owners respond by implementing dynamic mixed-use developments on large plots of land, optimizing land use, and integrating various functions such as residential, commercial, and recreational spaces within the same area. For larger areas, new buildings are added, and existing structures are demolished to comply with zoning adjustments and safety regulations. The insights provided by this research contribute to sustainable urban growth and efficient land use in Indonesia, emphasizing the need for strategic adaptability.